Strategies for the management and the development of the olive sector in the city of Skikda (Northeast of Algeria) - SAHLI, Samir (International Journal of Sciences and Natural Ressources, 2022)
Algerian olive growing is considered today as a strategic sector, it plays a very important role in the agricultural sector and has participated in the survival economy of communities over time. The region of Skikda is occupied the eighth place of olive oil producing regions in Algeria, it plays a potential role in the economic income of this sector. In this study we have drawn up a statistical inventory on the main agro-economic, socio-economic indicators, olive production situations, as well as a detailed report on the last agricultural campaign for 2020-2021, in order to establish a development plan. olive sector based on basic data, socio-economics activities and resources, the development strategy and some prospects at the end of this study to increase and improve the production and income of this sector.